“ANALYSIS OF THE CLASSROOM MANAGEMENT TECHNIQUES APPLIED FOR TEACHING ENGLISH LANGUAGE TO STUDENTS OF TENTH YEAR OF BASIC EDUCATION, CLASS “A” AT UNIDAD EDUCATIVA CRISTIANA “NAZARENO”, IN RIOBAMBA CITY, CHIMBORAZO PROVINCE, DURING THE ACADEMIC YEAR 2018-2019” - Abarca Alulema, Vannesa Alexandra (2019)
Teaching English is a process in which it is indispensable to use different methods, techniques, strategies, in order to complete successfully the learning and teaching process. Based on previous English teachers’ experiences, it is important to take into account that discipline is a factor that requires total attention in the classroom. This research carried out with the students of Tenth Year of Basic Education at Unidad Educativa Cristiana “Nazareno”, describes the importance of the appropriate application of classroom management techniques regarding to discipline to control and avoid misbehaviour and disruptions during English classes. Some factors related to discipline classroom management techniques were observed and analyzed in order to accomplish the objectives of the research. This work belongs to the qualitative approach; the level is exploratory, while the method used was ethnographic. The technique used for this research was direct observation and observation files were the instrument to collect reliable information to accomplish the research objectives. The results of the research can be appreciated in the brief analysis about the new trends for discipline techniques their influence, effectiveness, and students’ responses. Finally, it is important to add that this research can be used as a reference for future investigations about classroom management techniques regarding to discipline in order to help to the English teachers to facilitate the teaching-learning process.